Recombination induced by triple-helix-targeted DNA damage in mammalian cells. - Faruqi, A F (1996)
Gene therapy has been hindered by the low frequency of homologous recombination in mammalian cells. To stimulate recombination, we investigated the use of triple-helix-forming oligonucleotides (TFOs) to target DNA damage to a selected site within cells. By treating cells with TFOs linked to psoralen, recombination was induced within a simian virus 40 vector carrying two mutant copies of the supF tRNA reporter gene. Gene conversion events, as well as mutations at the target site, were also observed. The variety of products suggests that multiple cellular pathways can act on the targeted damage, and data showing that the triple helix can influence these pathways are presented. The ability to specifically induce recombination or gene conversion within mammalian cells by using TFOs may provide a new research tool and may eventually lead to novel applications in gene therapy.